Safety and efficacy of percutaneous device closure of large post tricuspid shunts in pediatric patients with severe PAH at short term and midterm follow up - H. Shah, Jayal; M. Thakkar, Bhavesh (International Journal of Medical Research and Review, 2016)
Background: Transcatheter closure of large post-tricuspid shunts in patients with severe pulmonary arterial hypertension remains a challenging problem. Among this unique subset of patients there is an entire spectrum of severity of pulmonary vascular disease with variable pulmonary vascular resistance and reversibility especially in older children. Aims: The current study was done to assess the safety and efficacy of percutaneous device closure of large post tricuspid shunts in pediatric patients with severe PAH at short and mid term follow up. Methods: A total of 42 pediatric patients underwent transcatheter closure of large post tricuspid shunts with severe PAH. All subjects underwent clinical examination, electrocardiography, chest x-rays and echocardiography before discharge and at 1, 6 and 12 months after the procedure and yearly thereafter. Results: Most of the patients (64 %) were having patent ductus arteriosus followed by ventricular septal defect in 8 patients (19.04%), aorto-pulmonary window in 5 patients (12%) and coronary cameral fistula in 2 patients (5%). Cardi-O-Fix VSD occluder was the most commonly used device (45%), Cardi-O-Fix PDA occluder (21%) and Amplatzer duct occluder in 17% patients. Pre-procedural pulmonary artery systolic pressure decreased significantly from mean 81.12 mmHg to mean 43.17 mmHg post procedure over a mean follow-up of 18.5 months. Only two major complications viz; severe aortic obstruction and symptomatic complete heart block were noticed in two children. Conclusions: Our study showed that the transcatheter closure of large post tricuspid shunts in pediatric patients with severe PAH was safe, feasible and efficacious alternative to conventional surgery.